Therapeutic approaches for pusher syndrome after a stroke: a literature review - Sayu Aryantari Putri Thanaya; Putu Eka Mardhika (Intisari Sains Medis, 2019)
Introduction: Pusher syndrome is a disorder that is clinically present in 5-52% of stroke patients, characterized by active pushing using the non-paretic side towards the paretic side, and resistance to the passive correction of posture. This disorder can pose an unfavorable effect on the rehabilitation of stroke patients. Hence, finding effective therapeutic approaches for pusher syndrome is crucial. This study aimed to identify the existing therapeutic approaches for pusher syndrome and investigate their effectiveness.Methods: A literature review was carried out, where studies were identified through searching the PubMed database from database inception to 2019 using the keywords: â€œpusher syndromeâ€, â€œpusher behaviourâ€, â€œcontraversive pushingâ€, â€œipsilateral pushingâ€, â€œlateropulsionâ€, â€œphysiotherapyâ€, â€œphysical therapyâ€, â€œtreatmentâ€, â€œtherapeutic approachâ€, â€œtherapyâ€ and â€œtrainingâ€. Â The literatures were analyzed systematically based on the results of previous studies.Results: Several approaches were identified for treating pusher syndrome post-stroke, including robot-assisted gait training (RAGT), galvanic vestibular stimulation (GVS), visual feedback (VF), and physiotherapy with additional components such as relaxation therapy in the prone position and lateral stepping with body weightâ€“supported treadmill training (LS-BWSTT). RAGT and VF training appear to be promising adjunctive approaches for treating pusher syndrome. Conventional physiotherapy with additional components such as relaxation therapy and LS-BWSTT have also led to positive effects. However, the effect of GVS has not been established.Conclusion: There is evidence that some therapeutic approaches can be beneficial for improving pusher syndrome and outcomes of stroke patients, in particular when combined with conventional physiotherapy. However, the number of studies is still very limited. Further research with methodological rigor is needed.